Analysis of Weaknesses of Administrative Fine Regulations in Countering Illegal Cigarette Circulation in Mataram City - Syahrurrozi Rumenah; Diana Lukitasari (Journal of Law, Politic and Humanities, 2026)
Analysis of the weaknesses of administrative fine regulations in countering the circulation of illegal cigarettes in Mataram City. This research is motivated by the still high circulation of illegal cigarettes in Mataram City even though law enforcement has been intensively carried out by the relevant authorities. This study aims to analyze the regulation of administrative fine sanctions in Law Number 39 of 2007 concerning Excise and examine the weaknesses of these regulations in providing a deterrent effect on violators. The research method used is normative juridical combined with an empirical approach through interviews and documentation studies. The results of the study show that the regulation of administrative fine sanctions is more oriented to the fiscal function, namely the recovery of state losses, rather than the function of deterrence against the perpetrators. In practice, the sanctions are not effective because the amount of the fine is not proportional to the perpetrator's profits, supervision is still limited, and the public's legal awareness is low. The conclusion of this study emphasizes that the weakness of administrative sanctions lies not only in the implementation, but also in the design of regulations that have not been able to accommodate the prevention function optimally.